Efektivitas Pelaksanaan Program Pelayanan Publik Plus di Kecamatan Kuranji Kota Padang - Susantri, Arni Eka (JESS (Journal of Education on Social Science); Vol 2 No 1 (2018): Social Issues in Public Service, 2018)
The purpose of this study was  to describe the effectiveness of the implementation of “ public service plus” programs in Kecamatan Kuranji Padang  City . This study describe d  the effectiveness of program implementation seen from the quality of apparatus, administrator competence, facilities and infrastructure, discipline, and supervision. This study was a  descriptive research with quantitative approach. The population of this study amounted to 1285 users of public services plus, with a sample of 93 respondents determined by Slovin formula and us ed  random sampling technique. Instrument in this study  use d  questionnaire with L ikert scale measurement. D ata in this study were analyzed with  descriptive statistic. The results of this study indicate d  that the effectiveness of the implementation of public service plus programs only reached 49.7% and categorized as quite  effective. In terms of effectiveness of the implementation of public service programs plus seen from the quality of apparatus, administrator competence, facilities and infrastructure, discipline and supervision, the service program only reached 57.3% and categor ized as quite effective.